New records and distribution extensions of three species of Mesoclemmys Gray, 1863 (Testudines: Chelidae) in Mato Grosso state, Brazil, with observations on terrestrial movements - de Brito, Elizângela Silva; Strüssmann, Christine; Kawashita-Ribeiro, Ricardo Alexandre; Morais, Drausio Honório [UNESP]; Ávila, Robson Waldemar; Campos, Vitor Azarias (My University, 2012)
Distribution patterns of most of the 20 Neotropical freshwater turtles belonging to the family Chelidae are usually based on few locality records. We here report on vouchered records of three species of the chelid genus Mesoclemmys in the Brazilian state of Mato Grosso. Presence of M. vanderhaegei is confirmed for the Amazon River Basin, and M. gibba and M. raniceps are recorded in Mato Grosso for the first time. © 2012 Check List and Authors.
Keywords: Chelidae; Phrynops; Raniceps; Testudines